Egg allergy - Turner,PJ; Campbell,DE (2017)
71Allergy to hen’s egg is perhaps the most common paediatric food allergy worldwide. This is certainly true for Australia and North America. It is unclear what makes this otherwise nutritious, innocuous and widely consumed food quite so allergenic. In this chapter we will examine the molecular characteristics and biochemistry of hen’s egg and the epidemiology, diagnosis, management and prevention of both IgE- and non-IgE mediated egg allergies.